Method Optimization for Rapid Measurement of Carbohydrates in Plasma by Liquid Chromatography Tandem Mass Spectrometry - Nguyen, Duc-Toan; Yu, Jundong; Mho, Sun-Il; Lee, Hae-Lee; Lee, Wonjae; Yee, Sung-Tae; Lee, Gwang; Paik, Man-Jeong (Bulletin of the Korean Chemical Society, 2013)
KCI Citation Count: 3